2017
DOI: 10.5120/cae2017652683
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating DC Voltage Temperature Coefficient of a Multicrystalline Module in Actual Environmental Conditions of Western Rajasthan, India

Abstract: Solar irradiance and cell temperature are the two most important parameters governing the efficiency of PV power plant. This paper presents simultaneous impact of cell temperature and the irradiance falling on the plane of solar panels-POA (Plane of Array Irradiance) on the dc voltage(V dc ) of a multicrystalline Photovoltaic(PV) module, one of the most important parameter governing dc power and hence efficiency of (PV) power plant. In contrast to existing literature which specify negative temperature coeffici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Garg, JB showed positive effect of ambient and cell temperature on dc voltage up to 38 o C and 50 o C respectively [20]. In another paper [21] Garg, JB showed significant positive effect of cell temperature in 49 o C to 62 o C range and that V dc attains nearly constant and high value only at high cell temperature. Garg, JB also showed that significant dc power is obtained only at high cell temperature [22].…”
Section: Introductionmentioning
confidence: 89%
“…Garg, JB showed positive effect of ambient and cell temperature on dc voltage up to 38 o C and 50 o C respectively [20]. In another paper [21] Garg, JB showed significant positive effect of cell temperature in 49 o C to 62 o C range and that V dc attains nearly constant and high value only at high cell temperature. Garg, JB also showed that significant dc power is obtained only at high cell temperature [22].…”
Section: Introductionmentioning
confidence: 89%
“…The results of Garg et al [5] also show that dc voltage decreases with increase in temperature only for ambient temperature greater than 38 o C and cell temperature greater than 50 o C. Garg et al [6] have shown that dc power output varies in direct proportion to irradiance outweighing the change in temperature. Power output at cell temperature 50-55 o C was far greater than power output at 40 o C. Garg and JB [7] have also shown that dc voltage attains a point of saturation maintaining nearly constant value in the range of 80-85% of its rated value for cell temperature greater than 49 o C. Mustapha et al [8] while evaluating the performance of a polycrystalline solar photovoltaic module under Maiduguri-Nigeria weather conditions have shown that current generated is directly proportional to solar irradiance and is almost independent of temperature. The maximum rated power was achieved during the sunniest month and module current increased by 0.1 A/ o C with increase in temperature, while module voltage decreased by 0.05 V/ o C leading to increase in power with increase in temperature.…”
Section: Introductionmentioning
confidence: 90%